Sure! Here are two examples of polynomial expressions with different degrees:
-
Polynomial A (Degree 3):
\[ P(x) = 2x^3 + 5x^2 - 3x + 4 \] -
Polynomial B (Degree 4):
\[ Q(x) = 4x^4 - x^3 + 2x - 7 \]
Sum of the Polynomials
To find the sum, we add the like terms of both polynomials.
\[ P(x) + Q(x) = (2x^3 + 5x^2 - 3x + 4) + (4x^4 - x^3 + 2x - 7) \]
Now, arranging and combining like terms:
\[ = 4x^4 + (2x^3 - x^3) + 5x^2 + (-3x + 2x) + (4 - 7) \] \[ = 4x^4 + x^3 + 5x^2 - x - 3 \]
Difference of the Polynomials
To find the difference, we subtract polynomial A from polynomial B.
\[ Q(x) - P(x) = (4x^4 - x^3 + 2x - 7) - (2x^3 + 5x^2 - 3x + 4) \]
Now, rearranging and combining like terms:
\[ = 4x^4 + (-x^3 - 2x^3) + (-5x^2) + (2x + 3x) + (-7 - 4) \] \[ = 4x^4 - 3x^3 - 5x^2 + 5x - 11 \]
Summary of Results
- Sum: \( S(x) = 4x^4 + x^3 + 5x^2 - x - 3 \)
- Difference: \( D(x) = 4x^4 - 3x^3 - 5x^2 + 5x - 11 \)
Common Mistake When Subtracting Polynomials
A common mistake when subtracting polynomials is forgetting to change the signs of all the terms in the polynomial being subtracted. For example, when subtracting polynomial A from polynomial B, one must distribute the negative sign to each term of polynomial A before combining like terms. Failing to do so will lead to incorrect results in the resultant polynomial.
For instance, if we mistakenly wrote:
\[ Q(x) - P(x) = (4x^4 - x^3 + 2x - 7) - (2x^3 + 5x^2 - 3x + 4) \]
and did not change the signs of the terms in \( P(x) \):
\[ = 4x^4 - x^3 + 2x - 7 - 2x^3 - 5x^2 + 3x + 4 \]
That would lead to combining as:
\[ = 4x^4 + (-1x^3 - 2x^3) + (-5x^2) + (2x + 3x) + (-7 + 4) \]
This results in an incorrect polynomial.